THE ROLE OF BMT BINA UMMAH IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS - Gea Desvi Asrul; Sartini Wardiwiyono (Universitas Tulungagung, 2026)
This study aims to analyze the role of BMT Bina Ummah in supporting the achievement of the Sustainable Development Goals (SDGs) through the integration of social functions (maal) and financing functions (tamwil). The research object is BMT Bina Ummah, located in Gamping, Sleman, Yogyakarta Special Region. The study used a qualitative approach with a case study design. Data were obtained through in-depth interviews, observations, focus group discussions (FGDs), and documentation. Data were then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicate that BMT Bina Ummah contributes to eight SDGs: no poverty, good health and well-being, quality education, clean water and sanitation, decent work and economic growth, reduced inequalities, sustainable cities and communities, and partnerships for the goals. These contributions are realized through sharia micro-enterprise financing, qardh hasan (Islamic loan), mudharabah savings, educational scholarships, the Rice ATM program, clean water provision, financial literacy, and social partnerships. This study concludes that BMTs function not only as Islamic microfinance institutions but also as instruments for promoting community economic and social empowerment.